Organisation questions of feather harvesting from live geese - Kozák, János (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
Harvesting feathers from live geese is defined as removing mature feathers from the back, flanks, belly and breast at time of their natural moulting. Feather maturity is to be tested by pilot gatherings. Feather harvesting can only be performed by hand under appropriate environmental conditions (average daily air temperature +15 °C, minimum temperature > +6°, bathing facility, vitamin and feed-supplements prior to feather gathering, empty digestive tract, etc.). For larger goose flocks several groups are organised performing the catching of birds, the harvesting of feathers (operators), treatment of feathers, and assisting the operators. For 2–3 operators one assistant, for 2–3 assistants one catcher and for 4–5 operators one feather treating person should be engaged in. The feather harvesting itself takes 6–10 minutes per goose. In order to protect geese and stimulate feather renewal geese require enclosure housing and more abundant feeding post harvesting. In Hungary, the keeping of the legal regulations of feather harvesting is supervised by official veterinarians.